Heterocontrole da fluoretação da água de abastecimento público em Pelotas e Rio Grande/RS e comparação de dois métodos de avaliação do fluoreto - Hasan, Nihad Hasan Musa (2007)
Fluorine addition in public water supply has been associated to the enormous world decline in dental caries index, still is the most efficiency preventive method for dental health. However the implementation of the fluoridation of the water propitiated the increase of the prevalence of dental fluorosis. The aim of this study were evaluate the level of fluorine in the public water supply in the cities of Pelotas and Rio Grande-RS and compare two fluorine determination methods. The samples were collected, biweekly, in the same points of the companies of public water supply in the two cities evaluated, Rio Grande (8 points), Pelotas (44 points). To the mensuration of the fluoride present in the samples two methods were used, one was the spectrophotometric SPANDS, the other the electrometric. The samples were appraised in duplicate and the results obtained was that the methods electrometric and espectrofotométrico presented good correlation (p<0,01), however there was difference statistics (p < 0,05).The concentrations of fluoride in the public water supply were inside of the values recommended in the twelve months of evaluation in the two districts of Pelotas and Rio Grande/RS. It was ended that of the two tested methods are suitable for determination of fluoride concentration, however the most precise is the electrometric. During the twelve months of surveillance in the two districts, the concentrations of the fluoride stayed in the recommended and didn't represent a risk to the dental fluorosis